Kajian Kinerja Simpang Bersinyal Bundaran Kecil Dan Simpang Tambun Bungai Di Palangka Raya Kalimantan Tengah - Ari Widya Permana; M. Zainul Arifin; Hendi Bowoputro (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2017)
Bundaran Kecil intersection is close to Tambun Bungai intersection, so vehicle must stop at each intersection because it gets red signal. To reduce delay and queue, signal coordination is required. Primary data include vehicle volume, geometric intersection and roundabout, signal timing, saturation flow, and travel time. Method used are Indonesian highway capacity manual (IHCM) 1997 and saturation flow approach method. From analysis, on roundabout, degree of saturation at weaving DA (R. T. A. Milono street - G. Obos street) reached 0.901. On signalized intersection, average delay value is > 60 sec/pcu (LOS F). Best scenario is 8th scenario with cycle time of 90 seconds and has LOS D. Based on coordination diagram obtained offset of 40 seconds and bandwidth of 13 seconds.